Unlocking the air and other stories - Le Guin, Ursula K., 1929- (New York : HarperPerennial, 2005)
Collection of eighteen stories written over the course of twelve years, from the early eighties to the mid-nineties, exploring the mysteries of name and time, and ordinary living and pain.
Library Journal
Pub Weekly
Wilson's Fiction
Adult.
Adult
Keywords: Manners and customs -- Fiction; Manners and customs -- Fiction; Short stories; Fantastic fiction